Study of the useful life of a structure in reinforced concrete: corrosion initiation by carbonation - Ana Paula Brandão Capraro; Poline Ariana Alves de Paula; Rafael Fernandes da Silva; Giovana Costa Réus; Marcelo Henrique Farias de Medeiros (Revista de Engenharia Civil IMED, 2019)
There is a direct relationship between the durability concrete structures and the environment in they are exposed. Studies can be developed to understanding of the degrading mechanisms acting on the structures is important, developed for the improvement of the materials, allowing the structures to be more durable under different environmental conditions. The present work presents a case study, with the objective of analyzing the useful life of a building, located in Curitiba-PR, being the same subject to continuous emission of CO2, coming from the urban environment. Considering the carbonation mechanism as one of the main responsible for triggering the corrosion of building reinforcements located in large urban centers, the research applied two models of useful life prediction, Tuutti (1982) and Possan (2010), to determine the useful life of the structure, taking in consideration only this phenomenon. As results, the work corroborated the idea that the internal pillars are more subject to the carbonation mechanism, because they are not in direct contact with the rainwater. In cases where had greater aggressiveness (internal pillars) was reached the life of the building, with an active corrosion process. In the external pillars, a more pleasant situation, the verified useful life is higher, getting closer and even surpassing the 50 years suggested by the Brazilian standad, NBR 15575 (2013).